2011
DOI: 10.1172/jci45472
|View full text |Cite
|
Sign up to set email alerts
|

Brain insulin action augments hepatic glycogen synthesis without suppressing glucose production or gluconeogenesis in dogs

Abstract: In rodents, acute brain insulin action reduces blood glucose levels by suppressing the expression of enzymes in the hepatic gluconeogenic pathway, thereby reducing gluconeogenesis and endogenous glucose production (EGP). Whether a similar mechanism is functional in large animals, including humans, is unknown. Here, we demonstrated that in canines, physiologic brain hyperinsulinemia brought about by infusion of insulin into the head arteries (during a pancreatic clamp to maintain basal hepatic insulin and gluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 43 publications
7
112
2
Order By: Relevance
“…Short duration pancreatic clamp studies in conscious dogs failed to show an acute impact on EGP when insulin delivery to the head was increased 4-fold (39). Further work in dogs confirmed the ability of ICV insulin infusion to increase hepatic STAT3 phosphorylation and suppress hepatic gluconeogenic enzyme expression (40). Although glucose production was not affected in this acute setting, net hepatic glucose output did slowly decrease over the course of these clamps.…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 82%
“…Short duration pancreatic clamp studies in conscious dogs failed to show an acute impact on EGP when insulin delivery to the head was increased 4-fold (39). Further work in dogs confirmed the ability of ICV insulin infusion to increase hepatic STAT3 phosphorylation and suppress hepatic gluconeogenic enzyme expression (40). Although glucose production was not affected in this acute setting, net hepatic glucose output did slowly decrease over the course of these clamps.…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 82%
“…However, it has been reported that while icv insulin activates hepatic STAT3 and suppresses gluconeogenic enzyme gene expression in dogs, their HGP is not reduced [49]. These findings indicate that while central insulin action-mediated mechanism that controls hepatic gluconeogenic enzyme expression is preserved across the species, its importance in whole body glucose metabolism differs greatly among the species.…”
Section: Central Insulin Action-mediated Hgp Control and Type 2 Diabementioning
confidence: 90%
“…As seen with food intake, glucose tolerance test and hyperinsulinemic-euglycemic clamp, STAT3 is activated in the liver following icv insulin administration and diazoxide administration [9,48,49]. On the other hand, STAT3 activation in the liver following glucose tolerance test is attenuated in NIRKO mice [9].…”
Section: Central Insulin Action Regulates Hgpmentioning
confidence: 99%
“…In the fasting state, the liver uses glycogen stores to mobilize glucose and maintain blood glucose levels [1,2] . In addition, the liver obtains glucose through gluconeogenesis.…”
Section: Introductionmentioning
confidence: 99%